‘Irfānī Epistemology: Revealing the Inner Meaning of the Qur’anic Verses in the Classical Interpretation - Mutawali Mutawali (Ulumuna, 2016)
Irfānī epistemology is one of the Islamic philosophical paradigms for understanding religious texts including the Qur'ānic texts. It maintains that the source of knowledge is intuition that puts emphasis on spiritual cultivation, not text or reason. Although this epistemology is criticized, it has been introduced Muslim scholars since the end of 4th and the beginning of 5th-century hijra as shown by Abū ‘Abd al-Raḥmān Sullāmī, Abū al-Ḥusayn Nūrī, Abū Manṣūr al-Ḥallāj and Ibn ‘Aṭā’ Allāh through their work Ḥaqā’iq al-Tafsīr. ‘Abd al-Karīm bin Hawazan Qushayrī, Ibn Sīnā, Ibn ‘Arabī, and Ṣadr al-Dīn Qunāwī, just to mention some, are the next generation of Muslim scholars who are concerned with it. This study examines the construction and the development of ‘irfānī epistemology as it is seen from the work of those scholars. It argues that ‘irfānī epistemology constitutes one important and fundamental Islamic episteme that serves to complete the other types of episteme, such as burhānī and bayānī. DOI: http://dx.doi.org/10.20414/ujis.v20i2.887